Learners’ Competencies as Influenced by Related Variables in Alternative Learning System Accreditation and Equivalency Testing - Moleño , Roleen B. (Research Developments in Science and Technology Vol. 1, 2022)
The objective of this research was to determine the variables that influence the learners’ competencies in Alternative Learning System (ALS). Specifically, it aimed to determine: the Accreditation and Equivalency (A and E) test takers’ socio-demographic characteristics; the ALS Instructional Managers’ (IM) socio-demographic characteristics; the extent of use of the mode of A and E program delivery by the IMs; the competencies of the learners in the A and E test based on overall results; the learners’ initial literacy level; whether the learners’ competency in A and E is significantly influenced by their socio-demographic characteristics; whether the learners’ competencies in the ALS A and E test is significantly influenced by the Instructional Managers’ socio-demographic characteristics; whether the learners’ competencies in ALS A and E are significantly influenced by the Instructional Managers’ extent of use of the mode of A and E program delivery; and whether the learners’ competency is significantly influenced by their initial literacy level. The study employed descriptive-correlational research design utilizing four (4) instruments. There were 1,824 ALS learners and 79 ALS Instructional Managers completely enumerated respondents of the study. In statistical tools, descriptive statistics and multiple regression were used. It was concluded in the study that: the face-to-face mode of delivery is the most preferred by the ALS Instructional Managers and ALS learners do not possess the needed competencies in the Sustainable Use of Resources and Productivity. The combined contribution of the initial literacy level did not significantly influence the learners’ competency in the areas of the A and E test such as Filipino Communication Skills, English Communication Skills, Mathematics and Science, Sustainable Use of Resources and Productivity, Expanding One’s World Views, Essay, and in the overall result. Furthermore, ALS students have not gained much competence throughout their formal school attendance, and their competency in the A and E test areas was not influenced by variables like their socio-demographic characteristics, IMs' socio-demographic characteristics, or their baseline literacy level.